Vampire diaries : The Fury and The Reunion / [Volume 2 (book 3 & 4)] - Smith, L. J., 1965- (Lisa Jane) (Hodder Children's Books, 2009)
The Fury: Faced with an ancient evil, Stefan and Damon must stop their feuding and join forces with Elena to confront it. But in so doing, they are unwittingly sealing her fate... The Reunion: Elena summons the vampire trio once more to unite and challenge their fate. Together they will be called to face the most terrifying evil Fell´s Church has ever known.